Innovation in Teaching Materials for Descriptive Texts: Introducing Local Tourist Attractions Using the Scan Me Application - Astuti, Fera Dwi; Harjito, Harjito; Septiana, Ika; Umaya, Nazla Maharani (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
ABSTRACTThe skill of writing descriptive text is a competency that must be mastered by grade VII students. However, in reality, many still have difficulty in expressing ideas for writing descriptive text. Contextual and irrelevant teaching materials are one of the triggers. Teaching materials using the scan me application by utilizing local tourist attractions are one of the solutions. The method used in this study is RD with eight stages of modification from Borg and Gall. Samples were taken from two schools, SMPN 1 Rembang and SMPN 3 Rembang with a total of 32 students from each school. Data collection techniques used questionnaires, interviews, and tests. The results of the study showed that the teaching materials developed were valid, practical, and effective in improving students' abilities in writing and understanding descriptive texts. The scan me application has proven to be an interactive and relevant media to students' learning styles in the digital era.Keywords: teaching materials, descriptive text, tourist attractions, scan me application